Exploiting Cysteine Residues of SLC Membrane Transporters as Targets for Drugs. (October 2019) - Scalise, Mariafrancesca; Console, Lara; Galluccio, Michele; Pochini, Lorena; Tonazzi, Annamaria; Giangregorio, Nicola; Indiveri, Cesare
The observation that cysteine is the top gainer amino acid during evolution attracted the attention of scientists dealing with protein chemistry. The thiol group of cysteine, indeed, is a potential site for several types of reactions with variable specificity and strength. This feature proved to be promising also in the field of membrane transporters that represent boundary proteins fundamental for cell homeostasis. These proteins are classified, according to the driving force for transport, in primary or secondary active transporters. Another frequently used classification is nowadays based on phylogenesis. Two major groups are identified that take into account both criteria: the ABC and the SLC transporters, the second being much more numerous. The cellular localization of the transporters makes them very attractive for drug design. Moreover, the presence of at least one cysteine residue in all the annotated SLC transporters, so far, highlights the possibility of using the thiol (SH) residue for covalent drug targeting. Even if a delay exists in this research field due to the scarce knowledge of structure/function relationships, the setup of novel experimental tools for studying SLC proteins of plasma and organelle membranes opens an important perspective in pharmacology.